Self-Efficacy Siswa Pengaruhnya terhadap Hasil Belajar Fikih - Firyal Yasmin RF; Qiqi Yuliati Zakiyah; Wildan Baihaqi (Gunung Djati Conference Series, 2022)
The enthusiasm of students seems to be reduced, many students are passive and depend on the teacher only when the teaching and learning process results in an average student score below the KKM score. This study aims to determine the students' self-efficacy towards their fiqh subject learning outcomes at MAN 1 Garut. This research uses a quantitative approach using the correlation method with applied research. The data collection used in this study were questionnaires, tests, and documentation studies obtained by 70 respondents. Based on the results of the study, it showed that students' self-efficacy was in the high category with an average score of 3.52 and fiqh learning outcomes were in the low category with an average score of 66.19 with the effect of student self-efficacy on fiqh learning outcomes of 12.8. % belongs to the low category with a correlation coefficient of 0.358 belonging to the low category which means that self-efficacy affects the fiqh learning outcomes by 12.8% and the rest is influenced by other variables not discussed in this study.